Abdominal Oblitoma, let's talk about a case (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2022)
Latin word, oblitum or forgotten; It is said that a foreign body is forgotten inside a patient during a surgical intervention (Spanish Royal Academy of Language), three types of response can be detected: encapsulated granulomatous, abscess with inflammatory exudate, painful and that migrates through the intestine to its lumen. Although it is a fortunately infrequent event, intra-abdominal foreign bodies continue to occur despite the precautions that have been taken; It not only has implication on the patient's health but also medical legal.In our case under discussion, it is a patient who underwent emergency surgery in a state of hypovolemic shock, in the early hours of the morning, with heavy bleeding and the use of many compresses during the surgical act, that is, with many criteria to present this condition. type of adverse eventPrevention is based on counting the surgical material before the surgical intervention and after it. If this count is not exact, the intervention site (cavities) or the radiological examination must be manually explored again.
Keywords: oblitoma; forgotten foreign body